A readout of metabolic efficiency in arylamine N‐acetyltransferase‐deficient mice reveals minor energy metabolism changes. Issue 8 (22nd March 2019) - Denis, Raphaël G.P.; Busi, Florent; Castel, Julien; Morel, Chloé; Zhang, Wenchao; Bui, Linh‐Chi; Sugamori, Kim S.; Prokopec, Stephenie D.; Boutros, Paul C.; Grant, Denis M.; Rodrigues‐Lima, Fernando; Luquet, Serge; et al.
Abstract : Recent studies have revealed a possible link between the activities of polymorphic arylamine N ‐acetyltransferases (NATs) and energy metabolism. We used a Nat1 / Nat2 double knockout (KO) mouse model to demonstrate that ablation of the two Nat genes is associated with modest, intermittent alterations in respiratory exchange rate. Pyruvate tolerance tests show that double KO mice have attenuated hepatic gluconeogenesis when maintained on a high‐fat/high‐sucrose diet. Absence of the two Nat genes also leads to an increase in the hepatic concentration of coenzyme A in mice fed a high‐fat/high‐sucrose diet. Our results suggest a modest involvement of NAT in energy metabolism in mice, which is consistent with the absence of major phenotypic deregulation of energy metabolism in slow human acetylators. Abstract :